Diet & nutrition profile: Tanzania - Amunga, Dorcas; Honeycutt, Sydney; Grant, Frederick K. E.; Kinabo, Joyce; Bliznashka, Lilia; Olney, Deanna K. (International Food Policy Research Institute, 2025)
Poor nutrition, suboptimal diets, and low fruit and vegetable (F&V) intake are key preventable risk factors for non-communicable diseases (NCDs) globally. From 2022 to 2024, the CGIAR Research Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH) designed and began implementation of an end-to-end approach to increase F&V intake and improve diet quality, nutrition, and health, while also enhancing livelihoods, empowering women and youth, and mitigating environmental impacts. Now under the CGIAR Science Program on Better Diets and Nutrition (BDN), implementation of the FRESH approach continues with the aim of addressing barriers to the desirability, affordability, accessibility, and availability of diverse, safe, and sustainable F&V in low- and middle-income countries (LMICs). Tanzania is one of the four original priority countries implementing this end-to-end approach to increase intake of F&V and other perishable nutrient-rich foods.